The use of discussion boards by first year business Information Systems 100 students - Bolt, Susan; Graber, Mark (Informing Science Press, 2011)
Business Information Systems 100 (BISI00) is a common core businessunit at Curtin Business School in Western Australia. The unit is offeredto first year Bachelor of Commerce students in face-to-face, distance oronline modes; over 1166 students were enrolled in BISI00 in Semester1 2009. In all modes of learning students were given access to a learningmanagement system (LMS) and encouraged to communicatethrough the discussion board. The use of such technology is expectedto enhance access, quality, interaction and flexibility (Eastman &Owens Swift, 2002; Eaton, 2003; Freedman, 2008). Moreover, Krentlerand Willis-Flurry (2005) found in their research with university businessschool students that the use of technologies such as discussion boardsand the Internet enhanced student learning. Similarly, learning managementsystems are used at Curtin Business School to enhance access,quality, interaction, engagement and learning. Curtin Business Schoolstudents are introduced to the FLECS-Blackboard learning managementsystem and encouraged to use the discussion board functionalitythrough first year common core units such as Business InformationSystems 100. Local Western Australian students attend lectures andtutorials and also have access to the FLECS-Blackboard learning managementsystem; access to the BIS 100 unit is online for all distanceeducation students. The same weekly content is delivered for bothgroups. Quantitative data were collected; students' use of discussionboards was monitored and comparisons made between usage at thebeginning and end of a semester. Also, the numbers of students whocontributed and posted to individual threads was monitored. Additionally,qualitative data were collected; key informants were asked for theiropinion on how best to enhance students' learning experiences throughthe use of learning management systems. In this paper, the researchers present their findings about the relationship between students' differentlevels of engagement with discussion boards and their learning outcomes